Benign prostatic hyperplasia: Who will benefit from surgical intervention? A single center experience. Issue 3 (August 2022) - Sharifiaghdas, Farzaneh; Khoiniha, Mohammad Reza; Basiri, Abbas; Bonakdar Hashemi, Milad; Borumandnia, Nasrin; Dadpour, Mehdi
Background: To evaluate the pre-operative factors affecting clinical response to prostate surgery in men with benign prostatic hyperplasia (BPH). Materials and methods: In this prospective cohort study, 172 patients who underwent surgical intervention for BPH (either as open prostatectomy ( n  = 78) or monopolar-trans-urethral resection of prostate ( n  = 94) from February 2017 to October 2019 were consecutively enrolled. Pre-operative conventional three-lumen urodynamic study and transabdominal sonography were performed for all patients to determine peak flow rate (Qmax), detrusor pressure at the peak flow rate (PdetQmax), post-void residual volume (PVR), presence of detrusor overactivity (DO), prostate volume and median lobe size, and bladder wall thickness with empty and full bladder. Uroflowmetry and cystoscopy were performed during follow-up, whenever indicated. Successful surgical outcome was defined as subjective satisfaction of the patient and a Qmax of more than 15 ml/s on post-operative uroflowmetry. Results: At 1-year follow-up, complete resolution of lower urinary tract syndrome (LUTS) was detected in 138 (80.2%) patients; however, 21 (12.2%) still had pure obstructive LUTS, 9 (5.2%) had pure storage LUTS, and 4 (2.3%) were still suffering from both storage and obstructive LUTS. After performing multivariable analysis, shorter duration of pre-operative medical treatment and higher pre-operative bladder contractility index (BCI) were found to be independent predictors of successful surgery ( p  = 0.012 and p  < 0.001, respectively). Results of the ROC curve analysis showed that a preoperative BCI level more than 90.95 and pre-surgical medical treatment duration less than 14.45 months have the most specificity and sensitivity to predict the success of surgical outcome. We also observed that the probability of recovery decreased considerably over time following surgery. Conclusion: Shorter duration of pre-operative medical treatment and increased pre-operative BCI can independently predict favorable outcome of BPH surgery. These factors could be used for better patient management and appropriate planning and consultation before BPH surgery.